2005
DOI: 10.1021/jp044166o
|View full text |Cite
|
Sign up to set email alerts
|

H2 and Cl2 Production in the Radiolysis of Calcium and Magnesium Chlorides and Hydroxides

Abstract: The production of H2 has been examined in the gamma-ray and 5 MeV He ion radiolysis of CaCl2.2H2O, CaCl2.6H2O, Ca(OH)2, MgCl2.2H2O, MgCl2.6H2O, and Mg(OH)2. The highest yield for the formation of H2 is observed in the gamma-radiolysis of MgCl2.2H2O (0.72 molecule/(100 eV), 75 nmol/J), but the yield decreases with dose due to the relative instability of the dihydrate. The H2 yields with the other compounds range from 0.04 to 0.2 molecule/(100 eV) (4.2-21 nmol/J), which is lower than that from pure water or 2 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Apart from a signal increase, the formation of borate salts on the surface was discovered . Numerous publications attest that also chlorine compounds are decomposed by ionising radiation, including X‐rays . Urch detected chloride peak characteristics in L 2,3 ‐M spectra of various oxy‐chloro‐anions previously published by Henke and explained this as a result of sample decomposition because of irradiation.…”
Section: Discussionmentioning
confidence: 84%
“…Apart from a signal increase, the formation of borate salts on the surface was discovered . Numerous publications attest that also chlorine compounds are decomposed by ionising radiation, including X‐rays . Urch detected chloride peak characteristics in L 2,3 ‐M spectra of various oxy‐chloro‐anions previously published by Henke and explained this as a result of sample decomposition because of irradiation.…”
Section: Discussionmentioning
confidence: 84%
“…Chamber o-rings and kapton windows are held together with PETE blocks on either side - the back PETE block connects the chamber to a support structure of the end station, with the chamber connected by polyether ether ketone (PEEK) tubing lines to and from the sample delivery and flushing system, the operation of which is described in the supplementary information.
Figure 4 ( a ) Photograph of the chamber ( b ) Sketch of the chamber ( c ) An exploded view of the chamber showing its component parts 1 : front block 2 , kapton windows 3 , o-rings 4 , the chamber block 5 , Inlet PEEK tubing 6 , Outlet PEEK tubing 7 , Back block that is connected to supporting structure.
…”
Section: Methodsmentioning
confidence: 99%
“…The lepidocrocite formation induced by the solid oxidation, observed in this work for the set III (carbon steel sample), occurs by the H 2 O 2 molecule into the irradiated solution with a non negligible concentration (about 7 10 -5 mol.L -1 ). This lepidocrocite formation has been described by authors with three steps: 1) the catalytic decomposition of H 2 O 2 onto the solid surface [4,11,26,27,33,37,38,51] (reaction 1) with formation of O 2 or OH according to the surface properties and the pH values of the solution [37,38,51], 2) the Fe oxidation by the O 2 or OH species (reaction 2) with iron(II) hydroxide Fe(OH) 2 formation [4,11] similar to the U(IV) oxidation displayed in a previous study [37], 3) the oxidation of this iron hydroxide by the H 2 O 2 species in order to create the lepidocrocite -Fe(III)OOH structure [4,11,13] (reaction 3) identified in our work by XPS and Raman spectroscopy. Any authors [50] have observed that H 2 addition have no effect onto the H 2 O 2 production, but the H 2 species can be involved into the neutralisation of hydroxyl radicals species at the solid surface.…”
Section: Parts B and C: H 2 O 2 Surface Decomposition And Lepidocrocimentioning
confidence: 99%
“…Most the pre-quoted works systems oxides/water has shown an increase of the H 2 radiolytic yield regarding the pure water system. Few proposed mechanisms can be involved in the enhancement of hydrogen production by irradiation at the solid surface: (i) the hydrogen enrichment of the solid surface implying the H + (H 2 O) cluster formation [2,3], (ii) the electron-hole pair formation and exciton migration induced by the solid irradiation [3,[26][27][28][30][31][32][33][34], (iii) the role of hydroxyl groups density onto the solid surface [28,29,32,35]. The oxidative species H 2 O 2 , produced by chemical surface decomposition mechanism [25-27, 36, 37], has been described as the main source to produce hydroxyl groups at the solid surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation